PENGARUH MOTIVASI BELAJAR DAN KESIAPAN BELAJAR SISWA PADA MATA PELAJARAN IPS SISWA KELAS VIII SMP NEGERI 7 PEMATANG SIANTAR TAHUN AJARAN 2023/2024 - Agam P. Marpaung; Herlina Hotmadinar Sianipar; Susy Alestriani Sibagariang (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to determine whether there is an effect of learning motivation and readiness to learn students in social studies subjects of class VIII students of SMP Negeri 7 Pematangsiantar. The variables in this study are learning motivation and learning readiness as independent variables and learning outcomes as the dependent variable. This type of research is quantitative descriptive research, with a population of all students in grades VIII-4 to VIII-8 at SMP Negeri 7 Pematangsiantar totaling 160 students and a research sample of 115 students selected using random sampling technique. Data collection techniques were carried out by observation and distributing questionnaires, while data analysis techniques used validity tests, reliability tests, normality tests, multiple linear regression tests, t tests, f tests and coefficient of determination tests. Based on the results of data analysis, it is stated that there is a significant influence between learning motivation on the learning outcomes of students in class VIII of SMP Negeri 7 Pematangsiantar, seen from the value of t_count 7.95 < t_table 1,658. Then, there is a significant influence between learning readiness on student learning outcomes, this result can be seen from the t_hitung value of 8.31> t_table 1.658, and it is concluded that Ho is rejected and Ha is accepted, meaning that the variables of learning motivation and learning readiness have an influence on the learning outcomes of students in grade VIII of SMP Negeri 7 Pematangsiantar. Then there is a joint or simultaneous influence between learning motivation and student learning readiness on learning outcomes, seen from the F_hitung value 7.10> F_table value 3.08. The test of the coefficient of determination R Square of the learning motivation variable is known to be 0.6561, which means that 65.61% of the learning motivation variable affects learning outcomes and for the learning readiness variable it is known to be 0.7225, which means that 72.25% of learning readiness affects student learning outcomes at SMP Negeri 7 Pematangsiantar.